Randomized controlled trial of an integrated approach to treating insomnia and improving the use of positive airway pressure therapy in veterans with comorbid insomnia disorder and obstructive sleep apnea. Issue 4 (21st November 2020) - Alessi, Cathy A; Fung, Constance H; Dzierzewski, Joseph M; Fiorentino, Lavinia; Stepnowsky, Carl; Rodriguez Tapia, Juan C; Song, Yeonsu; Zeidler, Michelle R; Josephson, Karen; Mitchell, Michael N; Jouldjian, Stella; Martin, Jennifer L
Abstract: Study Objectives: Cognitive behavioral therapy for insomnia (CBTI) for comorbid insomnia and obstructive sleep apnea (OSA) has had mixed results. We integrated CBTI with a positive airway pressure (PAP) adherence program and tested effects on sleep and PAP use. Methods: 125 veterans (mean age 63.2, 96% men, 39% non-Hispanic white, 26% black/African American, 18% Hispanic/Latino) with comorbid insomnia and newly-diagnosed OSA (apnea-hypopnea index ≥ 15) were randomized to 5-weekly sessions integrating CBTI with a PAP adherence program provided by a "sleep coach" (with behavioral sleep medicine supervision), or 5-weekly sleep education control sessions. Participants and assessment staff were blinded to group assignment. Outcomes (baseline, 3 and 6 months) included Pittsburgh Sleep Quality Index (PSQI), 7-day sleep diary (sleep onset latency [SOL-D], wake after sleep onset [WASO-D], sleep efficiency [SE-D]), 7-day actigraphy (SE-A), and objective PAP use (hours/night and nights ≥ 4 h). Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), and Functional Outcomes of Sleep Questionnaire-10 (FOSQ-10) were also collected. Results: Compared to controls, intervention participants showed greater improvement (baseline to 3 and 6 months, respectively) in PSQI (−3.2 and −1.7), SOL-D (−16.2 and −15.5 minutes), SE-D (10.5% and 8.5%), SE-A (4.4% and 2.6%) and more 90-day PAP use (1.3 and 0.9 more hours/night, 17.4 and 11.3 more nights PAP ≥ 4 h). 90-day PAP use at 3 months was 3.2 and 1.9 h/night in intervention versus controls. Intervention participants also had greater improvements in ISI, ESS, and FOSQ-10 (all p < 0.05). Conclusions: An intervention integrating CBTI with a PAP adherence program delivered by a supervised sleep coach improved sleep and PAP use in adults with comorbid insomnia and OSA. Trial Registration: ClinicalTrials.gov Study name: Novel Treatment of Comorbid Insomnia and Sleep Apnea in Older Veterans URL: https://clinicaltrials.gov/ct2/results?cond=&term=NCT02027558&cntry=&state=&city=&dist = Registration: NCT02027558